Fossil - Taylor, Paul D. (New York : Distributed by Random House, 1990)
A photo essay about different types of fossils, from bacteria and algae to birds and mammals.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
6.9
Keywords: Paleontology -- Juvenile literature; Fossils; Paleontology; Fossils